Lewis acid activation of Weiss' reagents ([PhI(Pyr)2]2+) with boranes and isolation of [PhI(4-DMAP)]2+. Issue 91 (2nd November 2021) - Bakro, Aseel; Sharp-Bucknall, Lachlan; Poynder, Tiffany B.; Clegg, Jack K.; Wilson, David J. D.; Dutton, Jason L.
Abstract : I(iii ) reagent [PhI(Pyr)2 ] 2+ (Weiss' reagent) can be activated with borane Lewis acids in which a pyridine ligand is abstracted giving a more reactive derivative of the reagents. Abstract : Abstraction of a pyridine ligand from Weiss' reagent ([PhI(Pyr)2 ] 2+ ) using BF3 -Et2 O was found to activate Weiss' reagent towards electrophilic aromatic substitution reactions. The activated species can be isolated when 4-DMAP is used as the pyridine ligand and was determined to be [PhI(4-DMAP)] 2+ in solution. The isolated cation was reactive in electrophilic aromatic substitution reactions towards mesitylene, xylene and toluene that Weiss' reagent itself does not react with.